At Limbe, Malawi: Space-placemaking through the integration of street trading practices - Mwawa, Major (School of Architecture, Planning and Geomatics, 2024)
This study addresses the current contestation and attitude towards street traders in the global south. It proposes a paradigm shift in the approaches that seek to exclude and marginalise street trading practices from cities, arguing that these practices should co-exist with what is regarded as formal. It suggests that architects should participate and learn from traders, understand their practices and experiences, and use such dynamics as design opportunities to integrate them into the urban fabric rather than suppressing their community-driven advances. It also suggests the need for city councils to effectively engage with traders and provide infrastructure that speaks to their urban realities and practices. The Limbe CBD, on James Street, in Blantyre, Malawi, is the study area for the project, where I engaged with traders and uncovered their spatial practices, experiences, and needs through the theories of everyday life, space-placemaking, and the kinetic city. Mainly, the traders expressed the need to be involved in all decision-making processes directly affecting them and the need for a platform that facilitates this civic engagement. As such, this design dissertation proposes a community hub with a flexible space that can become a market, and a space for meetings, events, and skills training workshops, either by organisations or among themselves, in so doing, also providing a platform for empowerment. In addition, they expressed the need for water supply, effective waste management, surface runoff and flood control solutions, ablutions, and shedding structures. This study covers some of these issues in a master plan and focuses on the hub as its facilitator to turn the area into a conducive environment for trading activities.